The Effect of Lifestyle, Self-Concept and Perceived Value on Purchasing Decisions Ice Cream Baskin Robbins in Giant Express Banjarmasin - Muhammad Rizky Rasiobar; A Alfiannor (Apollo: Journal of Tourism and Business, 2023)
This research is aimed to find out and analyze the effect of the influence of life style, self concept and perceived value partially to the purchase decision of ice cream Baskin Robbins at Banjarmasin. This type of research was explanatory research. The population was the people of Banjarmasin City who had purchased ice cream Baskin Robbins at Banjarmasin. The researcher implemented purposive sampling. The sample size was 75 people. The data were analyzed by using multiple linear regression analysis. The results showed that life style have a significant partial to effect on purchase decision of ice cream Baskin Robbins at Banjarmasin. While self-concept and perceived value have no significant effect partially on purchase decision of ice cream Baskin Robbins at Banjarmasin